Assessment of Serum Levels of Advanced Oxidation Protein Products in Type 2 Diabetic Patients with and without Retinopathy Taking Different Antidiabetic Treatments - Sara Asaad Kadhim; Eman Saadi Saleh; Aymen Dheaa Jaafer (Iraqi Journal of Pharmaceutical Sciences, 2023)
The goal of this study was to investigate the protein peroxidation role by measuring serum levels of advanced oxidation protein products (AOPP) in type 2 diabetic patients with or without retinopathy and comparing them to controls to see if circulating AOPP levels can be used as a detection biomarker for DR. And see which of the two widely used antidiabetic treatment groups had the most impact on this oxidative stress marker. The groups were divided into two subgroups: 1) 70 type 2 diabetic patients (36 male, 34 female), 35 with diabetic retinopathy (DR) and 35 with no evidence of DR, and 2) non-diabetic controls (11 male, 9 female) were chosen from Ibn AL-Haitham Hospital for Ophthalmology and a Specialized Center for Endocrinology and Diabetes. AOPP levels were significantly higher in diabetic patients with (12.5±5.6 ng/ml) or without DR (5.1±4 ng/ml) when compared to those of controls (1.45 0.8 ng/ml) (p<0.05). AOPP levels were higher in the late stage of DR compared to the early stage(14 3.15 ng/ml ) and ( 10 2.13 ng/ml) respectively so. Furthermore, Dipeptidyl peptidase-4 inhibitors (DPP-4 inhibitors) cause a better reduction in AOPP levels compared to Sulfonylureas (SUs) in the NDR group. Increased protein oxidation may involve in the pathogenesis and severity of DR and the serum AOPP levels have the prospect to become a marker for the diagnosis of DR. DPP-4 inhibitors were better in slowing the progression of the disease compared to SUs.